Effects of Clostridium perfringens beta2 toxin on apoptosis, inflammation, and barrier function of intestinal porcine epithelial cells. (October 2020) - Gao, Xiaoli; Yang, Qiaoli; Huang, Xiaoyu; Yan, Zunqiang; Zhang, Shengwei; Luo, Ruirui; Wang, Pengfei; Wang, Wei; Xie, Kaihui; Jiang, Tiantuan; Gun, Shuangbao
Abstract: Clostridium perfringens beta2 (CPB2) toxin is an important virulence factor that causes enteric diseases in both humans and animals. To investigate the underlying mechanism in CPB2-induced inflammation and damage in the small intestinal epithelium, intestinal porcine epithelial cells (IPEC-J2) were treated with recombinant CPB2 (rCPB2) toxin. The results showed that IPEC-J2 cell viability was decreased by rCPB2 toxin treatment in a dose- and time-dependent manner. Analysis of cell morphology and Annexin V-FTIC/PI staining revealed that rCPB2 toxin induces cell apoptosis. Indeed, the expression of caspase-3, caspase-8, and caspase-9 was significantly increased at both the mRNA and protein levels in IPEC-J2 cells treated with rCPB2 toxin. The caspase-3 inhibitor Ac-DEVD-CHO reduced rCPB2 toxin-induced cell apoptosis. Moreover, exposure to the toxin increased the expression of interleukin (IL)-6, IL-7, IL-12, and IL-1β, while decreasing that of transforming growth factor beta 1 ( TGFβ1 ). Additionally, rCPB2 toxin treatment also induced intestinal barrier dysfunction, as evidenced by the degradation of zonula occludens (ZO)-1, claudin-1, and E-cadherin, as well as an increase in paracellular permeability. Overall, the results indicated that rCPB2 toxin induces apoptosis and inflammation, in addition to impairing intestinal barrier function in IPEC-J2 cells. Our findings provide a foundation to better understand the pathogenesis of C. perfringens infection and inform strategies to effectively prevent and treat C. perfringens -induced enteric diseases. Highlights: Recombinant CPB2 toxin induces activation of caspase-3 signaling pathway and cell apoptosis. Recombinant CPB2 toxin increases proinflammatory cytokines expression and causes IPEC-J2 cells injury. Recombinant CPB2 toxin disrupts intestinal epithelial barrier function.